PENINGKATAN KEMAMPUAN KETERAMPILAN BERBICARA SISWA KELAS IV SD DALAM PEMBELAJARAN INTRODUCTION - Angyuningsih, Ni Wayan Eka (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2013)
Aspects of students' skills in speaking at the primary level is still lacking. In the English curriculum, students should be able to communicate verbally with correct speech. In learning Introduction material, students are expected to be able to communicate verbally with the direct method. With the use of the English language continually practiced in the classroom, students can improve their English properly. When the teacher guidance students through the direct method directly, their speaking skills improved successfully. This is shown in an increase in the ability to speak in five aspects of evaluation speech (grammar, vocabulary, fluency, pronunciation, and comprehension) in students from pre-test until the second cycle. At pra-treatment, students do not understand the use of the phrase, a good structure in self introduction. Any questions in English concerning the introduction of the personal data has not been understood by the students. In the first cycle, it has shown an increased understanding of the data, especially in answering the question in the introduction. In the second cycle, it has been improved with the ability to speak well, except for students who did not absorb the lessons (there are two students).
Keywords: speaking skill, direct method, pretreatment, first cycle,and second cycle